Calcule os quocientes:
a) a+ab/x² : 2+2b/3x
b) x²-4x/x²+1 : x²-16/2x²+2
c) x²+1/x²-2x+1 : x²+2x+1/x-1
Soluções para a tarefa
Respondido por
16
a) ![\frac{a(1+b)}{ x^{2} } . \frac{3x}{2(1+b)} = \frac{3a}{x} \frac{a(1+b)}{ x^{2} } . \frac{3x}{2(1+b)} = \frac{3a}{x}](https://tex.z-dn.net/?f=+%5Cfrac%7Ba%281%2Bb%29%7D%7B+x%5E%7B2%7D+%7D+.+%5Cfrac%7B3x%7D%7B2%281%2Bb%29%7D+%3D+%5Cfrac%7B3a%7D%7Bx%7D+)
b)![\frac{ x(x -4)}{ (x^{2} +1)}. \frac{2( x^{2} +1)}{(x-4)(x+4)} = \frac{2x}{x+4} \frac{ x(x -4)}{ (x^{2} +1)}. \frac{2( x^{2} +1)}{(x-4)(x+4)} = \frac{2x}{x+4}](https://tex.z-dn.net/?f=+%5Cfrac%7B+x%28x+-4%29%7D%7B+%28x%5E%7B2%7D+%2B1%29%7D.+%5Cfrac%7B2%28+x%5E%7B2%7D+%2B1%29%7D%7B%28x-4%29%28x%2B4%29%7D++%3D+%5Cfrac%7B2x%7D%7Bx%2B4%7D+)
c)![\frac{ x^{2} +1}{(x-1)(x-1)} . \frac{x-1}{ x^{2} +2x+1} = \frac{ x^{2} +1}{(x-1)( x^{2} +2x+1)} \frac{ x^{2} +1}{(x-1)(x-1)} . \frac{x-1}{ x^{2} +2x+1} = \frac{ x^{2} +1}{(x-1)( x^{2} +2x+1)}](https://tex.z-dn.net/?f=+%5Cfrac%7B+x%5E%7B2%7D+%2B1%7D%7B%28x-1%29%28x-1%29%7D+.+%5Cfrac%7Bx-1%7D%7B+x%5E%7B2%7D+%2B2x%2B1%7D+%3D+%5Cfrac%7B+x%5E%7B2%7D+%2B1%7D%7B%28x-1%29%28+x%5E%7B2%7D+%2B2x%2B1%29%7D+)
![= \frac{ x^{2} +1}{ x^{3} +2 x^{2} +x- x^{2} -2x-1} = \frac{ x^{2} +1}{ x^{3} +2 x^{2} +x- x^{2} -2x-1}](https://tex.z-dn.net/?f=%3D+%5Cfrac%7B+x%5E%7B2%7D+%2B1%7D%7B+x%5E%7B3%7D+%2B2+x%5E%7B2%7D+%2Bx-+x%5E%7B2%7D+-2x-1%7D+)
![= \frac{ x^{2} +1}{ x^{3}+ x^{2} -x-1 } = \frac{ x^{2} +1}{ x^{3}+ x^{2} -x-1 }](https://tex.z-dn.net/?f=%3D+%5Cfrac%7B+x%5E%7B2%7D+%2B1%7D%7B+x%5E%7B3%7D%2B+x%5E%7B2%7D+-x-1+%7D+)
b)
c)
Perguntas interessantes
Filosofia,
1 ano atrás
Direito,
1 ano atrás
História,
1 ano atrás
Matemática,
1 ano atrás
Geografia,
1 ano atrás
Geografia,
1 ano atrás
Matemática,
1 ano atrás